(untitled) (International journal of artificial intelligence, 2025)
This article supports the concept of transformative education, which is considered a process that encourages raising consciousness, critical thinking, personal development, and individualization. Through this, art and culture also impact a person’s spiritual life by fostering aspirations toward higher goals, promoting goodness, and enhancing feelings of kindness and compassion towards others.